(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of profitability ratios, represented by Net Profit Margin (NPM), Gross Profit Margin (GPM), and Return on Equity (ROE), on firm value as measured by Price to Book Value (PBV) at PT Indo Tambangraya Megah Tbk. The research employed a quantitative method with an associative approach. Secondary data were obtained from the company’s annual financial statements for the period 2012–2025 and analyzed using multiple linear regression with SPSS version 22. The results indicate that, partially, NPM has no significant effect on PBV with a significance value of 0.112, and GPM also has no significant effect on PBV with a significance value of 0.693. In contrast, ROE has a positive and significant effect on PBV with a significance value of 0.031. Simultaneously, NPM, GPM, and ROE do not significantly affect PBV, as indicated by a significance value of 0.088. The coefficient of determination (R²) of 0.465 shows that 46.5% of the variation in firm value can be explained by the three profitability variables, while the remaining 53.5% is influenced by other factors outside the research model. These findings indicate that ROE is the profitability indicator that plays the most important role in enhancing the firm value of PT Indo Tambangraya Megah Tbk.